ANALISIS STRATEGI BERSAING SBU MINERAL PT SUCOFINDO - , Ibnu Gumelar; , Prof. Dr. Goedono, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study is aimed to analyze the dynamic change of tren that occur currently, in external factors and internal factors which affecting the implemented strategy in the past and strategy formulation based on the anticipation to the dynamic change of external and internal factors. This is a descriptive research. Primary data source is audited companyâs annual report, systems, procedures and data retrieved from selected managers of SBU Mineral PT Sucofindo. The analysis of external environment is conducted by analyzing economic characteristic, Porterâs Five Forces, Driving Forces and Key Success Factors. The analysis of internal environment is conducted by analyzing functional capabilities, such as organization, human resources, financial, operational and marketing. Then the result is to be processed with SWOT analysis. Strategy formulation is conducted and followed by strategy evaluation. The final step is creating recommendations that will suit to be implemented at SBU Mineral PT Sucofindo.